2019
DOI: 10.1002/jia2.25407
|View full text |Cite
|
Sign up to set email alerts
|

Daily and event‐driven pre‐exposure prophylaxis for men who have sex with men in Belgium: results of a prospective cohort measuring adherence, sexual behaviour and STI incidence

Abstract: Introduction Pre‐Exposure Prophylaxis (PrEP) is highly effective in reducing the risk for HIV infection among men who have sex with men (MSM) and may have an important impact in slowing down the HIV epidemic. Concerns remain however about low adherence, increased risk behaviour and reduced condom use when using PrEP. The aim of this study was to assess these factors prospectively among MSM using daily and event‐driven PrEP in Belgium. Methods An open‐label prospective cohort study was conducted from October 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
100
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 92 publications
(114 citation statements)
references
References 32 publications
12
100
2
Order By: Relevance
“…Nevertheless, overall discontinuation rates in our study were comparatively low: other demonstration projects found similar rates over much shorter follow-up time [ 20 , 27 , 28 ] and higher discontinuation rates were observed in larger-scale clinical or primary care implementation settings [ 13 , 29 ]. As our project is one of the few offering a choice of PrEP regimens, PrEP discontinuation might be low when having access to an alternative, non-daily regimen.…”
Section: Discussioncontrasting
confidence: 51%
“…Nevertheless, overall discontinuation rates in our study were comparatively low: other demonstration projects found similar rates over much shorter follow-up time [ 20 , 27 , 28 ] and higher discontinuation rates were observed in larger-scale clinical or primary care implementation settings [ 13 , 29 ]. As our project is one of the few offering a choice of PrEP regimens, PrEP discontinuation might be low when having access to an alternative, non-daily regimen.…”
Section: Discussioncontrasting
confidence: 51%
“…Depending on how often it is taken, on-demand PrEP could use far fewer than half the number of pills for a daily regimen over a month. Recent studies in Belgium and Netherlands found that 19% to 30% of PrEP users switched their regimen during follow-up [5,31], suggesting that switching regimen is relatively common and that daily and on-demand PrEP regimens are fluid [31]. Instead of making daily and on-demand PrEP into two different regimens, it is more reasonable to tailor PrEP use basing on one's current risk or create a new "combined" dosing regimen.…”
Section: Discussionmentioning
confidence: 99%
“…Not wanting to take a daily pill was indicated by 23.3% of the participants as a reason for stopping PrEP. While the current guidelines in Germany endorse only daily PrEP use, other studies have found that PrEP also has a positive efficacy and safety profile when taken ‘on demand’ [ 12 , 38 ]. It would be interesting to investigate whether on-demand PrEP may be a suitable option for people who are unwilling to take a daily pill.…”
Section: Discussionmentioning
confidence: 99%